A Mixed-Methods Feasibility Study of Integrated Pediatric Complex Care: Experiences of Parents With Care and the Value of Parent Engagement in Research - Hlyva, Oksana; Rae, Charlene; Deibert, Shelby; Kamran, Rakhshan; Shaikh, Haniah; Thabane, Lehana; Rosenbaum, Peter; Klassen, Anne; Lim, Audrey (Frontiers in Rehabilitation Sciences, 2021)
Children with medical complexity (CMC) are among the most vulnerable children in society. These children and their families face challenges of fragmented care, and are at risk for poorer health outcomes. Families play a vital role in providing care and are tasked with navigating the complexities of healthcare systems. It is essential to understand the best ways to engage these families in research to improve care and optimize health of CMC. Objectives: This study explored parent engagement in the context of a feasibility study evaluating an integrated tertiary complex care (ITCC) clinic created to support CMC closer to home. The primary aims of this paper were: (1) to understand family experiences of care; and (2) to explore parent engagement in the study. Method: This mixed-methods feasibility study included three components. First, feedback from focus group was used to identify common themes that informed interviews with parents. Second, qualitative interviews were conducted with parents, informed by the interpretive description approach, to describe their family experience with care, including the ITCC clinic. Third, questionnaires were completed by parents, included demographic and cost information and three validated scales designed to measure caregiver strain, family-centered care and parental health. Recruitment rate, percent completion of the questionnaires, and open-ended comments were used to assess parent engagement in the study. Results: The focus groups involved 19 parents (14 females, 5 males). Findings identified the importance of CC team accessibility, local access to care and a family-centered approach to care delivery. Challenges noted were access to trained community nursing, fatigue and lack of respite affecting caregiver well-being. The qualitative interviews involved 17 parents. Several themes were identified including proximity and continuity of care; care coordination. Parents who received care through the ITCC clinic appreciated receiving care closer to home. Questionnaires were completed by 44 of 77 (57%) eligible parents. Only 24 (31%) completed the 6-month questionnaire. Challenges with study recruitment and follow-up were identified. Conclusion: This mixed-methods feasibility study illustrated that family engagement was a challenging yet necessary endeavor in order to understand how to tailor healthcare to meet the complex needs of families caring for CMC.